The Effect of Providing Exclusive Breastfeeding Counseling on the Self-Efficacy of Breastfeeding Mothers - Intan Dwi Puspitasari; Nurlailis Saadah; Rahayu Sumaningsih; Teta Puji Rahayu (International Journal of Advanced Health Science and Technology, 2024)
Exclusive breastfeeding is a baby's best food for growth and development in the first six months. Breastfeeding mothers need high confidence and self-efficacy that they can provide breastmilk for their babies. The provision of counseling services allows mothers to gain a comprehensive understanding of proper breastfeeding techniques and the benefits of breast milk for infants. This study aimed to determine the effect of exclusive breastfeeding counseling on breastfeeding mothers' self-efficacy.This study was a pre-experiment study with a one group pretest-postest design. The sample in this study amounted to 33 exclusive breastfeeding mothers ≤ 6 months which is the total pupulation. The data obtained were processed and analyzed with the Wilcoxon Signed Rank test.The results of the statistical test analysis showed a change in efficacy after counseling of 15.50 with a significance value (Sig.) of 0.000. That is, there is an effect of exclusive breastfeeding counseling on the self-efficacy of breastfeeding mothers.The conclusion of this study is that there is an effect of exclusive breastfeeding counseling on the self-efficacy of breastfeeding mothers. It is hoped that this research can be used as information to carry out midwifery care, so that officers can provide maximum services to improve the quality of health services, especially counseling and providing information about the importance of exclusive breastfeeding so that there is no drop out and breastfeeding continues for up to 2 years.